Research on Market Development and Innovation of Third-Party Automotive R&D Institutions - Che, Yunlong; Zhang, Dengquan (Scientific Journal of Technology, 2026)
Against the backdrop of rapid iteration in the new energy vehicle industry and continuous upgrading of automakers' R&D systems, third-party automotive R&D institutions, as a vital part of the automotive industry’s R&D chain, play a key role in compensating for automakers’ R&D shortcomings, optimizing the allocation of industrial technical resources, and driving industrial technological iteration. To explore the market-oriented operation and innovative development paths of third-party automotive R&D institutions, this paper relies on cooperation cases with typical domestic automakers, selects traditional automaker AA Motors and new energy vehicle startups BB Motors and CC Motors as research subjects, and reviews the practical experience of market development and project resource management of the institution. By analyzing the evolution of cooperation models, pain points, and demand differences among automakers at different development stages and of different types, it summarizes differentiated market development strategies for third-party R&D institutions targeting mature traditional automakers and emerging automakers, and extracts three core cooperation models: joint vehicle development, specialized technology construction, and government-enterprise-institute tripartite collaboration. Meanwhile, considering the current red ocean competition in the industry, it proposes innovative optimization solutions from four dimensions: business philosophy, team structure, customer classification, and technical system. The research indicates that third-party automotive R&D institutions must abandon the single-minded cost-effectiveness competition mindset, focus on forward-looking technology R&D, process system construction, and differentiated service optimization, and achieve long-term development through tiered customer operation, professional team configuration, and standardized technology accumulation. This study aims to provide practical reference and theoretical guidance for third-party automotive R&D institutions to optimize market layout, enhance industrial competitiveness, and achieve high-quality sustainable development.